Strategi Pengembangan Religius Culture Peserta Didik MTs Al-Fatimiyah - Maya Sayyidah (Ahad: Multidisciplinary Journal of Islamic Studies, 2025)
This study aims to determine how the development of religious culture for students. The subjects of this study were students of MTs. Al-Fathimiyah Banjarwati Paciran Lamongan. The type of research used is Qualitative, which produces data and is analyzed using descriptive methods. The data collected using interview techniques, Observation, and documentation. The results of this study are that there are several developments of Religious Culture in MTs. Al-Fathimiyah includes 5 dimensions, dimensions of belief, dimensions of practice, dimensions of experience, dimensions of knowledge and dimensions of consequences